Forward Modeling of the Phobos Tides and Applications to the First Martian Year of the InSight Mission. Issue 7 (27th July 2021) - Pou, L.; Nimmo, F.; Lognonné, P.; Mimoun, D.; Garcia, R. F.; Pinot, B.; Rivoldini, A.; Banfield, D.; Banerdt, W. B.
Abstract: The tidal response of Mars, due to the Sun and the Martian moons, Phobos and Deimos, provides information about the interior structure of Mars. By using the Very Broad Band (VBB) seismometer of Seismic Experiment for Interior Structure (SEIS) as a gravimeter on the surface of Mars, the InSight mission will provide the long‐period data suited to tidal analysis: most notably, the proximity of Phobos implies that degree 2, 3, 4, and further tides will be detectable by the VBB and are expected to provide information about the rheology at different depths within Mars. In order to expedite the recovery of these tidal signals in the SEIS measurements, we model the tides raised by Phobos using a tidal potential deduced from JPL Horizons ephemerides. From this potential, we calculate the expected tidal acceleration at InSight's location and gravimetric factors using a set of plausible interior models of Mars. To simulate the expected long period signal on the VBB seismometer, we use the InSight Auxiliary Payload Sensor Suite data to model the noise seen at low frequency by SEIS mainly due to temperature and pressure variations. Based on this synthetic signal, by applying filtering methods such as stacking and matched filtering to these synthetic data, we show that by recovering the gravimetric factors, it should be possible to constrain the state of the core and its size with an accuracy of 125 km after two Earth years. Plain Language Summary: On Mars since November 26, 2018, the NASA InSight mission made weather measurements of the atmosphere's temperature, wind, and pressure. It has also put a seismometer at the surface of Mars to see Mars quakes. However, the seismometer can also be used to measure the tides due to the Martian moon Phobos: by deforming the surface of the planet, the Phobos tides will create a change in the gravity at the surface of Mars, which can be recorded. As Phobos is closer to Mars than the Moon is to Earth, the shape of the tides on Mars is more complicated, but can be used to determine the interior structure of Mars. In particular, its deepest part, the core, is not well determined: it is still unsure whether it is liquid or solid, and how big it is. We model the expected tides at InSight's location and noises due to temperature and pressure variations based on the measurements made to guess what the seismometer will record. This study shows that after two Earth years, we should be able to see the Phobos tides accurately enough to know the core state and size with an accuracy of 125 km. Key Points: The Phobos tides of degree 2, 3, and 4 should be detectable by the Very Broad Band seismometer on InSight's Seismic Experiment for Interior Structure (SEIS) We model these tides, the Martian interior and SEIS low frequency noise with recent InSight data Over 2 Earth years, determining the core state and size with 125 km accuracy should be possible